IDENTIFICATION AND FORECASTING OF SHARP CHANGES IN ECONOMICAL SYSTEMS BY TRACKING OF LOCAL LYAPUNOV EXPONENTS - Malyuk, Dmitry; Boyarintsev, Georgy (International Journal of Computing, 2014)
An approach to detect sharp changes in economical systems was developed in this paper. We will give brief introduction in current methods of prediction of nonlinear and chaotic time-series and give definition of local Lyapunov exponents (LLE). Then author’s approach will be described. Also some numerical results and discussions will be given.